Camping as a strategy for sportive development: the model proposed for the brazilian handball (Research, Society and Development, 2020)
The objective was to analyze the formative proposal of the National Camp of Development and Technical Improvement of the Confederação Brasileira de Handebol. While studying ex-post facto, documents and images of the Campsites were consulted. The activities indicate a formative triad, articulated between training session, video analysis and competition, with rules and norms of behavior related to the content of the training sessions. The sessions guided the implantation of a standard systematized by the technical coordinator of the Confederation. It is concluded that the process of sports development, through the Camp, enables a learning environment immersed in positive values of the sport practice for young handball athletes.